Development of A School Information Portal Based on Google Sites as a Medium for School Publication and Promotion - Wibowo, Teguh Basuki; Rusmawati, Retno Danu; Rohman, Ujang (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to develop a School Information Portal based on Google Sites to be used as a medium for school publication and promotion. The research utilizes the Research and Development (R&D) model with the ADDIE method, involving one design expert, one media expert, one content/material expert, and 30 respondents from SD Negeri Karangmojo 2, Jombang Regency. The instruments used include design validation, media validation, content/material validation, and a user satisfaction questionnaire for the portal. The results show that the validity percentages from the design expert, media expert, and content/material expert are 93.33%, 92.30%, and 90%, respectively. These findings indicate that: (1) The development of the School Information Portal based on Google Sites has proven effective in improving the quality of school publication and promotion media; (2) The portal meets the school’s needs in delivering information efficiently and effectively; (3) The user satisfaction questionnaire results show that the level of user satisfaction with the school information portal is at a good/satisfied and very good/very satisfied level, with an average score range of 3.77 to 4.40. The development of the School Information Portal based on Google Sites has proven effective in enhancing the quality of media for school publication and promotion. This portal meets the school’s needs for effective and efficient information dissemination. This study also emphasizes the importance of considering user satisfaction with the school information portal as a medium for publication and promotion